Access to health and social protection policies by homeless people during the COVID-19 pandemic: a mixed-methods case study on tailored inter-sector care during a health emergency - Martins, Ana Luisa Jorge; de Souza, Anelise Andrade; da Silva, Gabriela Drummond Marques; Dantas, Ana Carolina de Moraes Teixeira Vilela; Marinho, Rafaela Alves; Fernandes, Luísa da Matta Machado; Oliveira, Ana Maria Caldeira; Magalhães Júnior, Helvécio Miranda; Paes-Sousa, Rômulo (Frontiers in Public Health, 2024)
Introduction The article analyzed homeless people's (HP) access to health and social protection policies and tailored inter-sector care, including emergency measures, during the COVID-19 pandemic in Belo Horizonte (BH), capital of Minas Gerais state, Brazil. It intended to provide data on HP and evaluate existing public policies focused on vulnerable populations during this health emergency. Methods The study adopted a mixed-methods design with triangulation of quantitative and qualitative data. Results Social cartography showed that in the early months of the pandemic, the health administration had difficulty reordering the health system, which experienced constant updates in the protocols but was nevertheless consolidated over the months. The evidence collected in the study showed that important emergency interventions in the municipality of BH involved activities that facilitated access by HP to the supply of services. Discussion The existence of national guidelines for inter-sector care for HP cannot be ruled out as a positive influence, although the municipalities are responsible for their implementation. Significantly, a health emergency was necessary to intensify the relationship between health and social protection services. Roving services were among those with the greatest positive evidence, with the least need for infrastructure to be replicated at the local level. In addition, the temporary supply of various inter-sector services, simultaneously with the provision of day shelters by organized civil society, was considered a key factor for expanding and intensifying networks of care for HP during the emergency phase. A plan exists to continue and expand this model in the future. The study concluded that understanding the inter-sector variables that impact HP contributes to better targeting of investments in interventions that work at the root causes of these issues or that increase the effectiveness of health and social protection systems.